Temporal analysis of rainfall precipitation behavior in the Metropolitan Region of Cariri (MRC), Brazil - Gomes de Sousa, Sostenes (2019)
The Brazilian semi-arid region encompasses 1,133 municipalities, occupying an area of 982,563.3 km² and a population of approximately 47 million inhabitants. Water scarcity in the Brazilian semi-arid and mainly in the northeast region is a problem residents face year after year. This region is characterized by having: almost eight months of rainfall absence; periodic droughts; frequent flooding of intermittent rivers and sandy, shallow, saline soils deficient in essential nutrients for the development of plants. Rain still represents the only reconstituent water source that feedsback river courses and recharges aquifers of the Northeast region. The study of rainfall series is fundamental for the management of water resources, development of projects of coexistence in the semi-arid regions and improvements for the development of agriculture and livestock, besides encouraging the region’s water sustainability. The objective of this study was to analyze rainfall behavior occurring in the last 31 years (1987-2017) in the Metropolitan Region of Cariri (MRC), Brazil, in view of identifying the characteristics of the regional rainfall regime. Along with the Cearense Foundation of Meteorology and Water Resources (FUNCEME), a monthly pluviometric data registry of the municipality was created based on historical data series. Parameter calculations were performed, such as: average, maximum, minimum and standard deviation. In this way, it was possible to verify that the municipalities that presented the highest rainfall indexes were Caririaçu, which registered 1632.0 mm in 2008 and Santana do Cariri with 1612.1 mm in 1996. It is worth noting that between 2016 and 2017 the annual rainfall received in most MRC municipalities was well below the average of the analyzed series.